Review of Deputy Nazeer Ahmad's Novel "Toubat al-Nusuh" and "Fasana Mubtala” (In terms of technique and locale) - Suleman, Humera; Subhani, Mamuna (sourcecoder, 2024)
It is crucial to understand the location and the technique of writing any novel or fiction since it explains the writer's understanding of his surroundings and the grip he has on his characters. The purpose of this paper is to examine the technique and location of Deputy Nazeer Ahmad's novels "Toubat al-Nusuh" and "Fasana Mubtala." In "Toubat al-Nusuh," Deputy Nazeer Ahmad employs a unique writing technique that captures the essence of storytelling. The novel is set in a rural village, providing a vivid portrayal of the local culture, traditions, and way of life. In Fasana Mubtala with a combination of first-person narration and multiple perspectives, Ahmad creates a dynamic and engaging narrative. Additionally, the novel is set in a bustling city, offering a rich depiction of the urban environment and its social dynamics. The local events and little unique things make the writing a historical piece that stores the culture of the people.